INTOLERANSI KAUM PURITAN PADA MASA KOLONIAL DI AMERIKA: DITINJAU DARI FILM THE SCARLET LETTER DAN THE CRUCIBLE (The Puritan Intolerance in the Colonial Period in America: as Reflected in The Scarlet Letter and The - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The study discusses Puritans migration process and religious intolerance toward people of different divinity in American society, particulary in the 19 and 20 century. This study employs library research in which the data were gathered from some sources: books, journals, novels, films, and internet. Besides, this study was conducted under interdisciplinary approach such as historical, cultural, sociological, and micro to macro. The result of this study shows that the migration of Puritan society occured because they opposed absolute power of government and church. Having settled in Massachusetts, America in order to find the religious freeÂ¬dom, the Puritan started to exploit other's religious freedom. Thus, the PuriÂ¬tan democracy left in paradox. Hawthorne and Miller criticized the Puritan through their literary work. The Puritan hunted, exiled, executed people who did not have the same belief as they were. This kinds of ethic were against American's democracy, equality, and freedom as written in the Declaration of Independence. Hawthorne and Miller also interpreted that religious behavior